Understanding mobile shopping consumers' continuance intention during covid-19 epidemic - Nguyen Ngoc Xinh; Dang Quan Tri; Nguyen Thanh Luan (Digital transformation for smart business - smart city in a post-pandemic world, 2022)
Coronavirus compelled to customers to use internet and make it habit in their daily routine. That reason why e-commerce industry is growing rapidly due to Covid- 19. Therefore, the aim of this study is to investigate the variables responsible for the persistence of mobile shopping intentions during the COVID-19 epidemic in Ho Chi Minh City by integrating perceived risks and social norm into Expectation Confirmation Theory. The survey is being conducted in Ho Chi Minh City and respondents were selected via non-probability, judgmental sampling method. Next, the study uses the partial least squares structural equation modeling method to investigate the relationship among variables. The study broadens and verify an integrative approach of continuity willingness, with a value in the inquiry of personal features, post-mobile shopping perspective, m-shopping experience, and continuance intention to use m-shopping. Besides, this study's contribution is to recognize how customers react to online purchasing; it is useful for organizations such as retailers, suppliers, and practitioners of fast-moving consumer products. The results showed that subjective norm has no effect on the intention to continue buying via mobile, which contradicts previous research. Moreover, confirmation increases consumers' satisfaction and inteniont to use mobile shopping, whilst perceived risks still have a huge impact on it.
Keywords: 650; Covid 19; Mobile shopping; ECT-IS; E-commerce